Teachers’ Ability to Apply Their Subject-Specific Knowledge in Instructional Settings—A Qualitative Comparative Study in the Subjects Mathematics and Economics - Jeschke, Colin; Kuhn, Christiane; Heinze, Aiso; Zlatkin-Troitschanskaia, Olga; Saas, Hannes; Lindmeier, Anke M. (Frontiers in Education, 2021)
To teach effectively, teachers need subject-specific knowledge, such as content knowledge and pedagogical content knowledge, but also an ability to apply that knowledge to master demanding classroom situations. However, there is no consensus in research whether this ability should be modeled as a subject-specific ability or as a generic ability. This question is important for effective teacher training and especially for out-of-field teaching. In this exploratory study, we investigate the subject-specificity of the ability to apply subject-specific knowledge with German secondary pre-service teachers who are equally trained to teach mathematics and economics. We administered paper-pencil tests for subject-specific knowledge in both subjects to 37 pre-service teachers. In addition, video vignettes of instructional situations were used to elicit their ability to apply that knowledge. N = 6 cases showed apt subject-specific knowledge in both subjects to be analyzed regarding knowledge application. Based on a qualitative analysis of 93 responses to the video vignettes, teachers’ ability to apply that knowledge was examined. Our findings indicate systematic qualitative differences in the pre-service teachers’ responses in mathematics and economics. The results favor a subject-specific conceptualization of teachers’ ability to apply subject-specific knowledge in instructional settings. This implies for teacher training that learning opportunities for promoting teachers’ ability to apply their subject-specific knowledge in instructional settings should be designed specifically for the subject that will be taught. Our study also suggests that out-of-field teachers require training in both knowledge and an ability to apply this knowledge in teaching another subject, as their ability to apply knowledge may not transfer from their field of expertise.